2021
DOI: 10.3390/agriculture11111150
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Culturable Endophytic Actinobacteria Isolated from High Yield Camellia oleifera and Their Plant Growth Promotion Potential

Abstract: Camellia oleifera Abel. is one of the world’s four famous woody oil trees and has drawn increasing attention because of its high commercial value. Endophytes are microorganisms inhabiting inside plant tissues, and their functions vary with the change of host status and environmental parameters. To deepen our understanding of the interactions between C. oleifera and their endophytic actinobacteria, the present study investigated the four endophytic actinobacterial composition-residing high-yield C. oleifera tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…Different ways used by microorganism to inhibit the growth of pathogens include the production of ammonia, HCN, siderophore, antifungal enzymes, and so on [47]. Among all isolates, eight, four, and one isolates produced ammonia, siderophore, and HCN, respectively, which is in agreement with the work of Chukwuneme et al [27] and Xu et al [38]. Previous studies showed that the production of extracellular hydrolytic enzymes (cellulase, amylase, pectinase, and protease) by endophytic microorganisms played indirect role in plant growth, by utilizing endospermic starch during germination and also form association with host plant by invading plant cell wall to colonize host root system [48].…”
Section: Discussionsupporting
confidence: 86%
“…Different ways used by microorganism to inhibit the growth of pathogens include the production of ammonia, HCN, siderophore, antifungal enzymes, and so on [47]. Among all isolates, eight, four, and one isolates produced ammonia, siderophore, and HCN, respectively, which is in agreement with the work of Chukwuneme et al [27] and Xu et al [38]. Previous studies showed that the production of extracellular hydrolytic enzymes (cellulase, amylase, pectinase, and protease) by endophytic microorganisms played indirect role in plant growth, by utilizing endospermic starch during germination and also form association with host plant by invading plant cell wall to colonize host root system [48].…”
Section: Discussionsupporting
confidence: 86%
“…The treatments showed enhanced biomass, height, and leaf number compared to the control. These findings are similar to earlier reports that demonstrated that actinobacteria confer benefits to host plants by boosting health and overall growth ( Passari et al., 2015 ; Passari et al., 2016a ; Vurukonda et al., 2018 ; Xu et al., 2021 ). The efficiency of the selected endophytes as PGP agents was further validated by two-way ANOVA and fold change analysis.…”
Section: Discussionsupporting
confidence: 92%
“…In the past few years, various endophytic actinobacterial members were reported for PGP activity. For example, endophytic Streptomyces and Amycolatopsis isolated from Camellia oleifera increased the growth of C. oleifera seedlings [ 72 ]. Similarly, Streptomyces spp.…”
Section: Actinobacteria Diversity Associated With Plants and Plant Gr...mentioning
confidence: 99%
“…and Amycolatopsis spp. were used in the hydroponic germination of wheat seeds, and promoted plant growth in terms of root and stem parts [ 72 ]. The genus Streptomyces was mostly dominant among the isolates recovered from leaf, stem, and root samples of tea, including Actinomadura , Kribbella , Nocardia , Kytococcus , Leifsonia , Microbacterium , Micromonospora , Mobilicoccus , Mycobacterium , Nocardiopsis , Piscicoccus , and Pseudonocardia , whereas Mobilicoccus and Piscicoccus were reported for the first time as plant endophytes [ 73 ].…”
Section: Actinobacteria Diversity Associated With Plants and Plant Gr...mentioning
confidence: 99%